COLOR IN CONTEMPORARY CLOTHING AND ITS ROLE IN NON-VERBAL COMMUNICATION - HÎRȚESCU, CRISTINA GABRIELA (Studiul Artelor şi Culturologie: Istorie, Teorie, Practică)
Color is an important element of expression and communication; therefore it plays an important role in contemporary clothing. Used as means of non-verbal communication since ancient times, the color worn continues to convey information to those around, but today these are different from the past. In this sense, in the present work, the author highlights the factors that determine today’s chromatic choices in clothing and the types of information transmitted through the colors worn, in a comparative analysis. Personal taste, temperament, mood, motivation, occasion are among the information communicated through clothing today. An important influence in contemporary society has the trend system that generates seasonal color palettes. Along with the so-called „color of the year”, these are synthetic visual expressions of global contexts, easily understood by most consumers